MODELING OF FIBER SUSPENSIONS FOR PREDICTION OF FIBER ORIENTATION IN INJECTION MOLDED POLYMER COMPOSITES - OUMER, AHMED NURYE (2012)
The most important phenomenon observed in fiber suspensiOns during injection molding composite manufacturing processes is flow induced fiber orientation. The orientation of fibers determines the mechanical and physical properties of the final molded part. Therefore, it is very important to fully understand the flow behavior of the polymer-fiber matrix inside the injection molding cavity in order to be able to accurately predict the fiber orientation. Efforts are continually required in order to improve the quality of fiber reinforced composite products, and the fiber size distribution and phase change for solidification of the suspending polymer have been recognized as important factors. One evident limitation of the current fiber orientation prediction models is that there is no size scale included in the analysis. Moreover, there are not many studies existing which take in to account simultaneous filling and solidification effects and the effect of various relevant parameters on the prediction of fiber orientation. This thesis was concerned with a detailed investigation of how the fibers orient in response to the flow of the suspension in arbitrary three dimensional injection molding cavities. Thus, a new mathematical model for the flow and constitutive equations of the suspension which takes into account the phase change of the suspension and variable fiber size distribution was built. The flow front during the filling process was traced using the volume of fluid method (VOF), while an enthalpy-based approach was applied to model the phase change for solidification. The developed mathematical model was solved numerically using the Finite Volume Method (FVM). The simulations were performed with the aid of open source CFD software called OpenFOAM.